2021
DOI: 10.3390/inorganics9080061
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of the Synthesis of Iron Antimony Sulfide Powders from Single Source Precursors

Abstract: The antimony-iron sulfide system in general does not produce alloys below 540 °C from traditional solid-state methods. However, single source precursors have been known to produce unexpected products that arise from kinetically trapped polymorphs. In this paper, we test the efficacy of this approach toward the Fe-Sb-S system. Antimony and iron diethyldithiocarbamate complexes of the form Sb[S2CN(Et2)]3 (1) and Fe[S2CN(Et2)]3 (2) were synthesised, characterised, and used as single-source precursors for the prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The copper­(II) and iron­(III) diethyldithiocarbamate precursors used in this study were synthesized by adapting previously published methods. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper­(II) and iron­(III) diethyldithiocarbamate precursors used in this study were synthesized by adapting previously published methods. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The copper(II) and iron(III) diethyldithiocarbamate precursors used in this study were synthesized by adapting previously published methods. 12,39,56 Bis(diethylthiocarbamato)copper(II), Cu(S 2 CN-(C 2 H 10 ) 2 ) 2 . Sodium diethyldithiocarbamate trihydrate (10 g, 44 mmol, 2.0 equiv) was dissolved in methanol (100 mL).…”
Section: N D S O D I U M D I E T H Y L D I T H I O C a R B A M A T E ...mentioning
confidence: 99%
“…A similar approach was used with mixtures of Sb(S 2 CNEt 2 ) 3 and Fe(S 2 CNEt 2 ) 3 to deposit thin films of Sb 2(1−x) Fe 2x S 3 (0 ≥ x ≥ 1) via AACVD at temperatures from 300 to 475 °C. 58 Thiolate and Selenolate Precursors. Thiolates have the general formula RS − and are one of the more common sulfurbound ligand types.…”
Section: ■ Precursor Designmentioning
confidence: 99%
“…Additionally, EDX mapping showed that the Mo and W distribution was uniform, which is consistent with the material being an alloy rather than a mixture of MoS 2 and WS 2 regions. A similar approach was used with mixtures of Sb­(S 2 CNEt 2 ) 3 and Fe­(S 2 CNEt 2 ) 3 to deposit thin films of Sb 2(1– x ) Fe 2 x S 3 (0 ≥ x ≥ 1) via AACVD at temperatures from 300 to 475 °C …”
Section: Precursor Designmentioning
confidence: 99%